A Non-cooperative Game-theoretic Distributed Control Approach for Power Quality Compensators - Burgos-Mellado, Claudio; Bucarey, Victor; Morales-Paredes, Helmo K. [UNESP]; Munoz-Carpintero, Diego; IEEE (Ieee, 2022)
This paper demonstrates that the Game Theory (GT) can be an effective tool for implementing a distributed control scheme for coordinating the compensation efforts of power quality compensators (PQCs) feeding a common unbalanced load. A non-cooperative game is formulated where each PQCs minimises its own interests, defined as the power losses that incur each PQC in carrying unbalanced power from its connection point in the system to the point of common coupling (PCC). By doing this, the whole system will move until it reaches a global equilibrium (the so-called Nash equilibrium). The power losses are calculated based on the conservative power theory (CPT), allowing the implementation of the proposal in the natural abc reference frame. A comparison (via simulations) between the proposed noncooperative distributed scheme and a cooperative distributed approach based on the consensus theory shows that the proposed non-cooperative game compensates the PCC with fewer overall losses than the consensus-based cooperative approach, improving the efficiency of the whole compensation system.
Keywords: << Power quality >>; << Distributed Generation >>; << Active Filter >>; << Grid forming >>; << Microgrid >>